Somatic Embryogenesis Initiation in Sugi (Japanese Cedar, Cryptomeria japonica D. Don): Responses from Male-Fertile, Male-Sterile, and Polycross-Pollinated-Derived Seed Explants - Tsuyoshi E. Maruyama; Saneyoshi Ueno; Yoshihisa Hosoi; Shin-Ichi Miyazawa; Hideki Mori; Takumi Kaneeda; Yukiko Bamba; Yukiko Itoh; Satoko Hirayama; Kiyohisa Kawakami; Yoshinari Moriguchi (Plants, 2021)
This study aimed to obtain information from several embryogenic cell (EC) genotypes analyzing the factors that affect somatic embryogenesis (SE) initiation in sugi (Cryptomeria japonica, Cupressaceae) to apply them in the improvement of protocols for efficient induction of embryogenic cell lines (ECLs). The results of several years of experiments including studies on the influence of initial explant, seed collection time, and explant genotype as the main factors affecting SE initiation from male-fertile, male-sterile, and polycross-pollinated-derived seeds are described. Initiation frequencies depending on the plant genotype varied from 1.35 to 57.06%. The best induction efficiency was achieved when seeds were collected on mid-July using the entire megagametophyte as initial explants. The extrusion of ECs started approximately after 2 weeks of culture, and the establishment of ECLs was observed mostly 4 weeks after extrusion on media with or without plant growth regulators (PGRs). Subsequently, induced ECLs were maintained and proliferated on media with PGRs by 2–3-week-interval subculture routines. Although, the initial explant, collection time, and culture condition played important roles in ECL induction, the genotype of the plant material of sugi was the most influential factor in SE initiation.